2023
DOI: 10.3390/rs15225333
|View full text |Cite
|
Sign up to set email alerts
|

On-Board Geometric Rectification for Micro-Satellite Based on Lightweight Feature Database

Linhui Wang,
Yuming Xiang,
Zhenzhou Wang
et al.

Abstract: On-board processing is increasingly prevalent due to its efficient utilization of satellite resources. Among these resources, geometric rectification can significantly enhance positioning accuracy for subsequent tasks, such as object detection. This approach mitigates the heavy burden on downlink bandwidth and minimizes time delays by transmitting targeted patches rather than raw data. However, existing rectification methods are often unsuitable due to the limitations and conditions imposed on satellites. Fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Zhang et al [16] verified the substitutability of the RPC model for the rigorous imaging model of SAR from both theoretical and experimental aspects, demonstrating the feasibility of using the RPC model to fit SAR image imaging. The experimental results showed that the RPC model can achieve high fitting accuracy for SAR systems of different resolutions and can be used for the photogrammetric processing of SAR images.…”
Section: Ortho-rectification Model Based On General Imagingmentioning
confidence: 93%
See 1 more Smart Citation
“…Zhang et al [16] verified the substitutability of the RPC model for the rigorous imaging model of SAR from both theoretical and experimental aspects, demonstrating the feasibility of using the RPC model to fit SAR image imaging. The experimental results showed that the RPC model can achieve high fitting accuracy for SAR systems of different resolutions and can be used for the photogrammetric processing of SAR images.…”
Section: Ortho-rectification Model Based On General Imagingmentioning
confidence: 93%
“…Therefore, in order to adapt to the joint processing of multi-source remote sensing image data, generic positioning models emerged, among which the most widely used is the Rational Function Model (RFM) [12][13][14][15]. RFM uses a rational polynomial form to fit the rigorous model and was initially used for the geolocation of optical images [16][17][18]. With continuous research by scientists, RFM began to be gradually applied to the geolocation of SAR images [19][20][21].…”
Section: Introductionmentioning
confidence: 99%